Investigation the role of T cells in the progression of reflux oesophagitis to Barrett's oesophagus and oesophageal adenocarcinoma - Kavanagh, Maria (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2016)
Oesophageal adenocarcinoma (OAC) is an inflammatory driven cancer that arises on a background of gastro-oesophageal reflux disease (GORD) and Barrett’s oesophagus (BO). T cells have been implicated in the initiation of oesophagitis in GORD; however, their role in the progression from oesophagitis to BO and OAC has not been fully elucidated. The hypothesis of this thesis was that factors present in the local oesophageal microenvironment in oesophagitis, BO and OAC could alter T cell phenotype and function and ultimately drive disease progression. As such we carried out a novel and in-depth analysis of T cell profile in the GORD-BO-OAC sequence; examined the in-depth composition of the local oesophageal microenvironment, and assessed its impact of T cell profile and function, identifying potential immunotherapeutic targets.
Keywords: Medicine, Ph.D.; PhD Trinity College Dublin, 2016